Calreticulin regulates TGF-β1-induced epithelial mesenchymal transition through modulating Smad signaling and calcium signaling. (September 2017) - Wu, Yanjiao; Xu, Xiaoli; Ma, Lunkun; Yi, Qian; Sun, Weichao; Tang, Liling
Abstract: As a Ca 2+ binding protein, calreticulin (CRT) has many functions and plays an important role in a variety of tumors. The role of CRT in TGF-β1-induced EMT is unknown. In this study, we demonstrated in vitro that TGF-β1-induced EMT elevated the expression of CRT in A549 lung cancer cells. Subsequently, we confirmed that overexpression CRT had no capacity to induce A549 cells EMT alone, but successfully enhanced TGF-β1-induced-EMT. Furthermore, knockdown of CRT in A549 cells significantly suppressed changes of EMT marks expression induced by TGF-β1. On treatment with TGF-β1, overexpression of CRT could enhance the phosphorylation of both Smad2 and Smad3. Consistently, the knockdown of CRT by siRNA-CRT could inhibit Smad signaling pathway activated by TGF-β1. These results indicated that CRT regulates EMT induced by TGF-β1 through Smad signaling pathway. Finally, TGF-β1-induced-EMT enhanced store-operated Ca 2+ influx in A549 cells. CRT knockdown was able to abolish the effect of TGF-β1 on thapsigargin (TG) −induced Ca 2+ release, but had failed to reduce store-operated Ca 2+ influx. The alteration of intracellular Ca 2+ concentration by TG or BAPTA-AM was able to regulate EMT induced by TGF-β1 through Smad signaling pathway. Together, these data identify that CRT regulates TGF-β1-induced-EMT through modulating Smad signaling. Furthermore, TGF-β1-induced-EMT is highly calcium-dependent, CRT was partly involved in it.